PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK BERKIRIM SALAM DAN SOAL TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 35 PADANG - Nidawati, Nidawati; Anggraini, Villia; Cesaria, Anna (Pendidikan Matematika, 2014)
ABSTRACTÂ This research was conducted due to the studentsâ low understanding of mathematics concept and their inability to express ideas and answer the questions given. The aim of this research was to reveal whether the mathematics conceptual understanding of the students taught by applyingÂ  cooperative learning model sending greeting technique and question was better than that of students taught by applying conventional learning in class VIII of SMPN 35 Padang. This was an experimental research which used random toward the subject design. The population of the research was the students in class VIII ofÂ  SMPN 35 Padang registered in academic year 2013/2014. The instrument of the research was an essay posttest whose reliability =Â  0.86. Based on the result of data analysis Â by using t-test of the side, it was found that the value of = 2.33 was higher than = 1.67 indicating that the mathematics conceptual understanding of the students taught by applying cooperative learning model sending greeting Â technique Â and question was better than that of students taught by applying conventional learning in class VIII of SMPN 35 Padang